Learning Language Levels in Students Accurate with a History Academic Achievement History - Noorlela binti Noordin; Abdul Razaq Ahmad; Anuar Ahmad (Yupa: Historical Studies Journal, 2017)
This study was aimed to evaluate the Malay proficiency among students in Form Two especially non-Malay students and its relationship to academic achievement History. To achieve the purpose of the study there are two objectives, the first is to look at the difference between mean of Malay Language test influences min of academic achievement of History subject among non-Malay students in Form Two and the second is the relationship between the level of Malay proficiency and their academic achievement for History. This study used quantitative methods, which involved 100 people of Form Two non-Malay students in one of the schools in Klang, Selangor. This study used quantitative data were analyzed using descriptive statistics and statistical inference with IBM SPSS Statistics v22 software. This study found that there was a relationship between the proficiency of Malay language among non-Malay students with achievements in the subject of History. The implications of this study are discussed in this article.